Optimization of the carbonization process based on the evolution of microstructural components of polyacrylonitrile (PAN)-based fibers - Choi, Jiho; Jeon, Changbeom; Lee, Jung-Eun; Lee, Ga-Hyeun; Hwang, Sunjae; Han, Minjung; Lee, Seunghwan; Gwak, Hyeon Jung; Lee, Eunhye; Won, Jong Sung; Lee, Man Young; Chae, Han Gi; et al. (Pergamon Press Ltd., 2025)
This work presents a new approach for optimizing the carbonization conditions of polyacrylonitrile (PAN)-based fibers by tracing the microstructural changes during the carbonization process. Variations in the radial direction of the carbon fibers were also examined, emphasizing their correlation with temperature and duration. Changes in the outermost structure (surface) and radial heterogeneity were strongly correlated with tensile strength. Furthermore, the analysis focuses on structural changes in carbon crystallites and voids, which were analyzed using X-ray techniques, including wide-angle X-ray diffraction (WAXD) and small-angle X-ray scattering (SAXS). The size of the carbon crystallites increased exponentially with carbonization temperature and duration, forming master curves for crystallite-related properties, such as tensile modulus and void dimensions, with an identical shifting factor. These results suggest that structural changes in the radial direction critically affect mechanical properties. Based on these analyses, an optimal carbonization process was proposed, involving a duration of 2 min at 1300 degrees C, which resulted in a tensile strength of 3.97 GPa and a tensile modulus of 234 GPa. These findings offer a framework for optimizing the carbonization conditions to enhance the production of high-quality carbon fibers.